Moral Choice and Responsibility in Professional Conduct of Judges - Tatyana Aleksandrovna Ladykina (Сибирское юридическое обозрение, 2011)
The article is concerned with philosophical concepts of freedom and responsibility. The authors is focused on judicial ethical code, namely to the problem of moral choice and responsibility of judges. Approaches to understanding of the role of the court in the society. Such moral qualities of a judge as humanism, justice, honesty allow for making the right choice: to achieve a goal, one should use only legitimate means.